1993
DOI: 10.1111/j.1365-2958.1993.tb01960.x
|View full text |Cite
|
Sign up to set email alerts
|

A lowered concentration of cAMP receptor protein caused by glucose is an important determinant for catabolite repression in Escherichia coli

Abstract: A decreased intracellular concentration of cAMP is insufficient to account for catabolite repression in Escherichia coli. We show that glucose lowers the amount of cAMP receptor protein (CRP) in cells. A correlation exists between CRP and beta-galactosidase levels in cells growing under various conditions. Exogenous cAMP completely eliminates catabolite repression in CRP-overproducing cells, while it does not fully reverse the effect of glucose on beta-galactosidase expression in wild-type cells. When the CRP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
114
0
2

Year Published

1994
1994
2008
2008

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(124 citation statements)
references
References 31 publications
8
114
0
2
Order By: Relevance
“…This indicates that during diauxic growth the variation of cAMP concentration is much more important than the variation of CRP concentrations, which have almost no effect. This is in accordance with results from Ishizuka et al (19) who reported that variation of cAMP concentration is responsible for transient repression, whereas the lowering of the CRP concentration becomes important for permanent repression. This indicates that the regulation by variation of cAMP concentrations is important for fast, dynamic processes, e.g.…”
Section: Regulation Of Pts Operon and Ptsg Expression By Camp⅐crp Andsupporting
confidence: 82%
“…This indicates that during diauxic growth the variation of cAMP concentration is much more important than the variation of CRP concentrations, which have almost no effect. This is in accordance with results from Ishizuka et al (19) who reported that variation of cAMP concentration is responsible for transient repression, whereas the lowering of the CRP concentration becomes important for permanent repression. This indicates that the regulation by variation of cAMP concentrations is important for fast, dynamic processes, e.g.…”
Section: Regulation Of Pts Operon and Ptsg Expression By Camp⅐crp Andsupporting
confidence: 82%
“…2). The probable reason for the reduction of the activity of the P0 promoter when the mlc-negative strain grows in the presence of glucose is that the concentration of an activator of the P0 promoter, CRP⅐cAMP, was lowered in that condition (1,6). These results also indicated that the action of Mlc in the regulation of the pts operon is dominant over that of CRP⅐cAMP as proposed for the regulation of ptsG expression by Mlc recently (9).…”
Section: Discussionsupporting
confidence: 63%
“…Transcription of the pts promoters increases in the presence of CRP⅐cAMP as well as glucose in vivo (3,4). The glucose-and cAMP-mediated activations occur independently of each other (2,4,5), even though glucose lowers the level of CRP and cAMP in the cell (6). It has been known that the target promoter that is activated when cells are grown in the presence of glucose is the P0 promoter, but the mechanism by which glucose activates the P0 transcription is not known.…”
mentioning
confidence: 99%
“…To solubilize cells, the cell suspensions were mixed with 500 L of 2 2 loading buffer (4% SDS, 10% 2-mercaptoethanol, 125 mM Tris-HCl, pH 8.0, 20% glycerol, 0.2% bromophenol blue) and heated for 10 min at 100 8 C. Total proteins of the indicated amount were loaded onto 0.1% SDS-13% polyacrylamide gels and electrophoresed. After electrophoresis, Western blotting was performed as described previously (Ishizuka et al 1993), using a polyclonal anti-CRP antibody and a horseradish peroxidaseconjugated secondary antibody.…”
Section: Immunoblot Analysis Of Crpmentioning
confidence: 99%